Assessment of open versus closed modalities of breast abscess treatments: a cross sectional comparative study - Parakh, Aaditya M.; Diwakar, Mahendra K. (International Surgery Journal, 2018)
Background: Breast abscesses, localized collection of pus in the breast, are most common in young lactating women. Objectives of the study were to compare open versus closed modalities of treatment of breast abscess and to isolate the commonest organism responsible for breast abscess. Methods: A cross sectional prospective study was conducted in Department of Surgery or Department of Obstetrics and Gynecology from October 2009 to October 2011 among the breast abscess cases (both open and closed). The study was conducted in a group of 84 cases of breast abscess, divided in to two groups, the open group comprising of 46 cases and closed group comprising of 38 cases. Results: The incidence of abscess was most commonly seen in young women between the age group 15 – 25 years (59.5%). Breast abscess was found more commonly in lactating women (78.6%), with the mean duration of lactation of 24.93 days. The most common side involved was the right breast (64.28%). The upper half of the breast, predominantly the upper outer quadrant (58.33%) was affected, least common being lower inner quadrant (3.57%). Conclusions: On comparing the two methods of treatment of breast abscesses, the primary closure technique was superior to the conventional technique in terms of duration of healing, post operative pain, number of dressings required, length of hospitalization and post operative complications and quality of healing.